MANAJEMEN PROMOSI BERBASIS TEKNOLOGI INFORMASI DAN KOMUNIKASI DI SEKOLAH DASAR ISLAM SABILINA BEKASI - Rohman, Ahmad Minanur; Qulyubi, M Mujib; Leksono, Aris Adi; Khori, Ahmad (Laboratorium Jurusan S1 Manajemen Pendidikan Islam, 2024)
The background to this research is the enormous technological advances, especially in the fields of information and communication. One of the schools that implements the use of information and communication technology as a means of promotion is Sabilina Islamic Elementary School, Bekasi. This research aims to find out how the promotion management process is based on information and communication technology which includes the planning process, organizing, implementation, promotion, evaluation, and promotion results using information and communication technology at Sabilina Islamic Elementary School. This research uses qualitative research with a case study approach. The object of this research at Sabilina Islamic Elementary School, Bekasi. This research data collection technique uses interview, observation and documentation techniques. The analysis techniques used include data collection, data reduction, data presentation, and conclusion. The results of this research show that Sabilina Islamic Elementary School uses several media in its promotion, including social media, Facebook, Instagram, and websites. In the promotion management process, Sabilina Islamic Elementary School implements several stages. First, is promotion planning, which includes determining targets for selecting content and so on. Second, Sabilina Islamic Elementary Schools created special teams for this implementation which have been divided into their respective divisions of work. Third, create content according to a predetermined plan. Fourth, the promotion evaluation process is carried out once a year, namely at the end of each year so that the promotion process can continue to develop well. Fifth, from this research positive results were obtained in the promotion process using information and communication technology at Sabilina Islamic Elementary School. This can be seen from the many positive responses from parents of students and the number of prospective parents of students who interact on social media at Sabilina Islamic Elementary School